Using microbial indicator to assessment the pollution that resulting from the discharge of domestic wastewater to Al-Diwaniya river / Iraq - Al-Taee, Mysoon M.; Al-Kasser, Mohammed K. (Al-Qadisiyah Journal of Pure Science, 2017)
The discharge of untreated or incomplete treated domestic wastewater to receiving water is result to addition of many pollutants particularly pathogenic microorganisms, which has causing various diseases to aquatic organisms and humans are using this water, so that this study is executed to evaluate the microbial pollution resulting from the discharge of domestic wastewater to Al-Diwaniya river by measuring the total bacterial count (TBC) and most probable number of coliforms (TC), fecal coliforms (FC) and fecal streptococcus (FS). The samples are collected monthly for one year from four stations on the river, first located at the north of wastewater discharge point and it’s used as controlled station, and three stations located at the south of discharge point. The results are showed elevation in number of all bacterial types in station two, three and four comparison with the station one, and the numbers range are between (17.33Ã—102 - 310Ã—104) cell/ml , (4.2 - 403.3Ã—102) , (3 - 273.3Ã—102) , (29 - 1100Ã—102) cell/100ml for TBC, TC, FC and FS respectively. The study results showed that the numbers of pollution indicating bacteria are outside the permissible limits of World Health Organization (WHO) for waters which are using for drinking, moreover it’s exceeded permissible limits for swimming and recreational waters